Предмет: Математика, автор: bravlller72

Обчислити повністю \frac{\sqrt{7}- \sqrt{3}}{\sqrt{7}+ \sqrt{3}} +\frac{\sqrt{7}+ \sqrt{3}}{\sqrt{7}- \sqrt{3}}

Ответы

Автор ответа: arinchikd
1

Ответ:

5

Пошаговое объяснение:

\frac{\sqrt{7} -\sqrt{3} }{\sqrt{7} +\sqrt{3} } +\frac{\sqrt{7} +\sqrt{3} }{\sqrt{7} -\sqrt{3} } =\frac{(\sqrt{7} -\sqrt{3} )(\sqrt{7} -\sqrt{3} )+(\sqrt{7} +\sqrt{3} )(\sqrt{7} +\sqrt{3} )}{(\sqrt{7} +\sqrt{3} )(\sqrt{7} -\sqrt{3} )} =\\=\frac{7-2\sqrt{7*3} +3+7+2\sqrt{7*3} +3}{7-3} =\frac{20}{4} =5

Похожие вопросы
Предмет: Алгебра, автор: vnastasiya
Предмет: Биология, автор: thatssun